Odpowiedzi

2010-01-22T19:02:37+01:00

3)2x+3(1-x)=3-x
4)x+3(2-x)/2=-1/6+-3-x/3

1)x-3/2=x+1
-3/2 =1
równanie sprzeczne

2)5x+6-2x=4
3x=-2
x=-2/3

3)2x +3-3x=3-x
-x+3=3-x
0=0
równanie tożsamościowe

4)x+3-3/2x=-1/6-3-x/3
6x+18-9x=-1-18-2x
-3x+18=-19-2x
x = -37
Najlepsza Odpowiedź!
2010-01-22T19:06:26+01:00
1)1/2*(2x-3)=x+1
x-1,5=x+1
0x=2,5
sprzeczność

2)5x+2(3-x)=4
5x+6-2x=4
3x=-2 |:3
x=-2/3

3)2x+3(1-x)=3-x
2x+3-3x=3-x
-x+3=3-x
0=0
tożsamość

4)x+3(2-x)/2=-1/6+-3-x/3
(x+6-3x):2=-1/6-3-x/3
0,5x+3-1,5x=-1/6x-1/3x-3
-x+3=-0,5x-3
-0,5x=-6 |:-0,5
x=12
2010-01-22T19:25:10+01:00
1. x-3/2=x+1
0=2,5 rownanie sprzeczne
2. 5x+6-2x=4
3x=-2
x=-2/3
3. 2x+3-3x=3-x
0=0 wyrazenie tozsamosciowe
4. x+3-3x/2=-1/6-3-x/3
-1/2x +3=-1/6-3-x/3
-3/6x = -3-1/6-3-2/6x
-1/6x=-6-1/6
x=37